O caso acusativo nos pronomes pessoais de terceira pessoa do português brasileiro e europeu - Rodrigues, Lorena da Silva (2018)
This thesis aims to study the change in the pronominal system in Portuguese, in its European and Brazilian variants, regarding the category of case. Thereto, it considers that any change comes from an earlier stage of linguistic variation (Weinreich, Labov, Herzog, 2006; Labov, 1978, 1994, 2001, 2008, 2010) and investigates variants of pronouns o (a, os, as); ele (ela, eles, elas); lhe(s), in addition to zero anaphora. As conditioning factors of this change, it analyzes the oral or written continuum; the semantic properties of the direct object; the kind of verbal form that the accusative complements; the position of the pronoun; the historical period; the sex of the informant; the level of schooling; the age and the location. It proposes that the loss of the distinction of the case category in personal pronouns in Portuguese derives from the secular linguistic drift, and an evidence that proves this fact lies in the linguistic convergence of variants of Portuguese geographically distant but sharing cognitive and cultural factors (Labov, 2010) within Lusophony. It works with two samples, a written one and an oral one, containing texts from the 1970s to 2010 of Brazilian Portuguese and European Portuguese, as well as a test of perception and evaluation of variants applied to students of the University of Madeira. After being described, the data were subjected to a statistical treatment in the GoldVarb X program and then analyzed in the light of Sociofunctionalism, since, besides the Theory of Variation and Linguistic Change, it is based on the functionalist principles of iconicity and marking (Givon, 1979b, 1984, 1995, 2002, 2005, 2009, 2011). From the result of the test applied to 412 informants from Funchal, it was possible to map prestige variants and those stigmatized in European Portuguese peninsular. By order of evaluation, in an increasing sense of appreciation, the variants are distributed as it follows: ele, lhe, zero anaphora and o(a)(s). After that, it makes the analysis of the data of written and oral texts in European Portuguese and Brazilian Portuguese. For variant o, the following groups of factors were selected as conditioning factors: a) Age group (56 to 75); b) education level (high school and higher education); c) textual genre (news and editorial); d) historical period (decades of 70 and 2000); e) semantic property of the direct object (+human); f) type of verbal form (compound); g) locality (Lisbon and Funchal); and h) continuum speech vs. writing (writing). As for the pronoun ele, five factors were selected, namely: a) age12 range (36 to 55 and 56 to 75); b) schooling (elementary education); c) gender of the informant (female); d) locality (Rio de Janeiro); and e) semantic property of the direct object (+human). As for zero anaphora, the following factors were selected: a) age range (18 to 35); b) textual genre (interview); c) continuum speech vs. writing (speech); d) historical period (decades of 80, 90, 2010); e) locality (Rio de Janeiro); f) semantic trait of the object (–human) and g) type of the verbal form (simple). As for the pronoun lhe, only one conditioning factor was selected, the semantic property of the object (+human). After analyzing the data, functional microdomains were observed, configuring a syntax of the postcolonial Portuguese language: on the one hand, clitic o and zero anaphora, variants not marked, presenting high frequency, but opposite motivations; on the other hand, the variants marked cognitively and socially (ele and lhe) present low frequency and behavior analogous to each other.